Building the Professionalism of Islamic Religious Education Teachers in the Digital Era - Nur Ahlam; Herfina Adianti; Afidh Qolbinuril Auliya (PC Ikatan Sarjana Nahdlatul Ulama Ponorogo, 2025)
The rapid development of digital technology has drastically transformed the world of education and significantly impacted the demands placed on Islamic Religious Education (PAI) teachers. This study aims to investigate how PAI teachers build and enhance their professionalism amidst the digital transformation. Using a descriptive qualitative approach, data was collected through in-depth interviews, classroom observations, and document analysis involving teachers from various educational institutions. The results indicate that PAI teachers generally recognize the importance of digital literacy as a crucial part of their professional expertise and have begun integrating various digital tools such as learning management systems, multimedia content, and Quran-based applications into their teaching methods. Teachers employ a variety of strategies to improve their digital and pedagogical skills, including participating in training programs, self-study, and collaboration with colleagues. However, structural challenges such as limited technological infrastructure, a lack of relevant training, and uneven digital literacy levels among teachers hinder optimal implementation. This study concludes that strengthening PAI teacher professionalism in the digital era requires systemic support, appropriate training, infrastructure improvements, and continuous pedagogical innovation to maintain Islamic values ​​in technology-based learning.